Patient “No-Show” Prior to Elective Primary Total Hip Arthroplasty Increases Risk of Postoperative Anemia - Jeffrey S. Mun, BA; Matthew W. Parry, MD, MS; Alex Tang, MD; Jesse J. Manikowski, MS; Cory Crinella, PA-C; John J. Mercuri, MD, MA (Arthroplasty Today)
Background: Patients who “no-show” (NS) clinical appointments are at a higher risk of poor healthcare outcomes. The objective of this study was to evaluate and characterize the relationship between patient NS prior to primary total hip arthroplasty (THA) and 90-day complication risk after THA. Methods: We retrospectively reviewed 4147 patients undergoing primary THA. Patients were divided based on whether they NS at least 1 appointment vs always attend (AA) appointments. Information collected included number of NS and attended appointments, demographics, comorbidities, and 90-day postoperative complications. Regression analyses were run to identify relationships between NS status and postoperative outcomes, as well as factors that would predict NS status. Results: Compared to AA patients, NS patients had an increased odds of a postoperative complication (odds ratio:1.3, P = .0005), specifically postoperative anemia (odds ratio: 1.3, P = .0004). When comparing NS and AA patients who both experienced postoperative anemia-related complications, the NS patients had significantly greater intraoperative blood loss compared to AA patients (mean ± standard deviation: 412.6 mL ± 310.2 vs 357.3 mL ± 269.0, P = .028). NS patients also had a greater rate of symptomatic anemia compared to AA patients (100 [3%] vs 25 cases [2%], P = .018). Age, smoking status, gender, race, body mass index, Charlson Comorbidity Index, and insurance status were independent predictors of missing clinical appointments. Conclusions: There was an increased risk for complications, specifically anemia-related complications, in THA patients who NS preoperatively. Demographic factors were independently associated with higher odds of missing a scheduled clinical appointment. The results suggest orthopedic surgeons should consider NS data to pre-emptively assess risk for complications following THA. Level of Evidence: Level III.